Motivations for avoiding wheat consumption in Australia: results from a population survey. Issue 3 (17th April 2014) - Golley, Sinéad; Corsini, Nadia; Topping, David; Morell, Matthew; Mohr, Philip
Abstract Objective To assess the prevalence of and explanations for wheat avoidance, including reported symptoms, diagnoses and information sources influencing the decision to avoid wheat, and to investigate potential psychological predictors of this behaviour. Design Cross-sectional population survey. Setting The study was conducted in Australia, using a nationwide postal omnibus survey. Subjects Adults aged 18 years and over (n 1184; 52·9 % female) selected at random from the Australian Electoral Roll. Results With cases of stated and suspected coeliac disease (1·2 %) excluded, 7·3 % of the sample reported adverse physiological effects, predominantly gastrointestinal, that they associated with wheat consumption. Few among this group (5·7 %) claimed a formally diagnosed intolerance or allergy requiring avoidance of wheat-based foods. Symptomatic wheat avoidance was highly correlated with dairy avoidance and predicted by gender (female), lesser receptiveness to conventional medicine and greater receptiveness to complementary medicine, but not by neuroticism, reasoning style or tendency to worry about illness. Conclusions The data indicate that many adult Australians are consciously avoiding consumption of wheat foods, predominantly without any formal diagnosis. Reported symptoms suggest a physiological but not allergenic basis to this behaviour. Questions to be answered concern whether symptoms are attributed correctly to wheat, the agents (wheat components, dietary factors or additives) and physiological mechanism(s) involved, the nutritional adequacy of avoiders' diets, and the clinical and psychosocial processes that lead a substantial number of adults to avoid consuming wheat (or any other dietary factor) apparently independently of a medical diagnosis.